2009
DOI: 10.1103/physrevb.79.153106
|View full text |Cite
|
Sign up to set email alerts
|

In situphotoemission study ofNd1xSrxMnO3epitaxial thin films

Abstract: We have performed an in situ photoemission study of Nd 1−x Sr x MnO 3 ͑NSMO͒ thin films grown on SrTiO 3 ͑001͒ substrates by laser molecular-beam epitaxy. The lattice constants of the thin films were relaxed from those of the substrates, and the transport properties were almost the same as those of bulk NSMO. From core-level photoemission studies, we found that the behavior of the chemical-potential shift was not much different from that of the bulk NSMO samples. In the valence-band spectra, finite intensity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Thus, an electron in an occupied state experiences more attractive ionic potential due to relatively less screening offered by one less electron, leading to lowering of valence band energy and widening of the band gap. However, features such as composition and widths of the bands in our calculations are consistent with XPS, XES and XAS analyses of epitaxial thin lms grown by pulsed laser deposition, 27 and bulk crystals prepared by solid-state reactions. 28 Fig.…”
Section: Resultssupporting
confidence: 84%
“…Thus, an electron in an occupied state experiences more attractive ionic potential due to relatively less screening offered by one less electron, leading to lowering of valence band energy and widening of the band gap. However, features such as composition and widths of the bands in our calculations are consistent with XPS, XES and XAS analyses of epitaxial thin lms grown by pulsed laser deposition, 27 and bulk crystals prepared by solid-state reactions. 28 Fig.…”
Section: Resultssupporting
confidence: 84%
“…At −3 and −4 V gate biases, however, there is a clear shift and broadening of the XRD film peak, from the as‐grown pseudocubic (002) SrFeO 2.5 peak at ≈45.1° ( c ‐axis lattice parameter = 4.01 Å) toward higher angle, corresponding to a lattice contraction indicative of SrFeO 3‐δ oxidation. Corroborating this behavior in the absorption spectra is the development of a low‐energy absorption feature at ≈1.5 eV, which has been attributed to a mid‐bandgap hole‐doped state in SrFeO 3‐δ , [ 51 ] as well as an evident red‐shift in the spectral weight of absorptive intensity as previously reported via thermal treatment. [ 41 ] To quantify the oxidation, the XRD pattern obtained from −3 V gating was modeled as a bilayer of perovskite SrFeO 3‐δ overlaying brownmillerite SrFeO 2.5 .…”
Section: Resultssupporting
confidence: 52%
“…However, only few studies have been reported on the electronic structure of the series. [15][16][17][18] Soft x-ray absorption and electron spectroscopies have revealed that holes created by Sr doping have a mixed Fe 3d -O 2p character for high Sr content whereas they are mainly of the O 2p character for low Sr content. 15 Combined studies with photoemission spectroscopy have confirmed this point and suggested that the hole ordering on the oxygen sites plays an essential role in realizing the charge disproportionated state.…”
Section: Introductionmentioning
confidence: 99%
“…15 Combined studies with photoemission spectroscopy have confirmed this point and suggested that the hole ordering on the oxygen sites plays an essential role in realizing the charge disproportionated state. 16 The present work was undertaken with the aim of gaining insight into the changes of the electronic and local structure of Fe atoms upon varying the La/ Sr ratio. It also focuses on the changes observed at the so-called CO transition at the critical concentrations of x =2/ 3 and x =3/ 4.…”
Section: Introductionmentioning
confidence: 99%